An Analysis of Hamster Afferent Taste Nerve Response Functions - Frank, Marion (The Rockefeller University Press, 1973)
Sensitivities to moderately intense stimuli representing four taste qualities to man were determined for 79 hamster chorda tympani fibers. Some fibers were very sensitive to sucrose, sodium chloride, or hydrochloric acid, but none were very sensitive to quinine. These sensitivities were not randomly distributed among fibers: the sucrose sensitivity was separated from and negatively correlated with the other sensitivities which were associated and positively correlated with each other. Moreover, there were a limited number of sensitivity patterns: (a) fibers responding best to sucrose responded second-best to salt, less to acid, not to quinine; (b) fibers responding best to salt either responded second-best to sucrose and not to acid or quinine; or second-best to acid, less to quinine, and not to sucrose; and (c) fibers responding best to acid responded second-best to salt, more to quinine, and less to sucrose than other fibers. Therefore, if four stimuli of different taste qualities are ordered from acceptable to unacceptable, neural response functions of most hamster chorda tympani taste fibers peak at one point. Sensitivities to nine other moderately intense stimuli which vary in quality to man were also determined for 46–49 of the fibers. Sensitivities to sweet stimuli were always associated with each other and separated from sensitivities to nonsweet stimuli. Sensitivities to nonsweet stimuli were all associated with each other; however, the strongest correlations were between sensitivities to stimuli of like quality, e.g., the three acids or the two sodium salts.